Antiphotobleaching: A Type of Structurally Rigid Chromophore Ready for Constructing Highly Luminescent and Highly Photostable Europium Complexes. (10th February 2016) - Wei, Huibo; Zhao, Zifeng; Wei, Chen; Yu, Gang; Liu, Zhiwei; Zhang, Bin; Bian, Jiang; Bian, Zuqiang; Huang, Chunhui
Abstract : Antiphotobleaching is a critical challenge in the field of luminescent lanthanide complexes (LLCs) as well as in many disciplines concerning organic luminescent processes. In this work, a type of structurally rigid organic ligand, 4‐hydroxy‐1, 5‐naphthyridine (ND), is developed, which can not only efficiently sensitize the europium emission but also demonstrate unique photostability. A series of ND derivatives with different substituent groups are synthesized and their singlet and triplet excited state energy levels are systematically investigated. Photophysical characterizations of the corresponding europium complexes reveal that the sensitization efficiencies ( η sens ) are close to 100% and the total photoluminescence quantum yields can reach up to 84%. Most importantly, these structurally rigid luminescent europium complexes exhibit outstanding photostability and thermostability. Unlike the widely used β‐diketone complexes that are easily photodegraded, ND‐based chelates show no obvious degradation during the UV aging test (10 W m −2 340 nm Ultraviolet A irradiation) within 200 h. Such superior UV resistance is even better than that of the famous compound tris(8‐hydroxyquinolate)aluminum (Alq3 ). Possible reasons are discussed and a general rule for designing photostable LLCs is proposed. Such a chromophore is very promising for introducing luminescent materials with good photostability in potential application in many disciplines. Abstract : Highly luminescent europium complexes are produced by using a series of 8‐hydroxyquinoline derived ligands with an enlarged energy gap and a rigid aromatic structure. The complexes are highly photostable even under high energy UV irradiation, unlike the traditional β‐diketone complexes.